MASSIVE SULFIDE ORES OF THE URALS: A NEW GENERAL MINERALOGICAL OBJECT - Chesnokov B.V.; Zaikov V.V.; Melekestseva I.Yu. (My University, 2003)
The main pyrite deposits in Ural region are concentrated in Tagilskaya and Magnitogorskaya metallogenic zones formed in middle Paleozoic period. These structures have length of 1,500 km and width of several tens km. They are characterized by the leading positions in respect with reserves of Co plus Pb plus Zn (55 million tons). About 20 deposits are exploited. The minerals of pyrite ores have been investigated. Results of the investigations have been presented. Symmetry constants of the minerals correspond to constants of general objects. It has been shown that the ore formation is connected with generation of magma.